PARTISPATORY DEVELOPMENT COMMUNICATION: OPTIMALISASI PERAN PEREMPUAN DALAM PROGRAM PEMBERDAYAAN PEREMPUAN DPMGP4 KABUPATEN NAGAN RAYA - Reni Juliani; Putri Maulina; Desi Maulida (JURNAL TRIAS POLITIKA, 2023)
ABSTRACTWomen have the ability to play a role as strategic actors in Indonesia's development, as well as women from Nagan Raya District. The purpose of this research is to dig deeper into optimizing the role of women in women's empowerment programs in partnership with the Office of Community Empowerment, Gampong, Population Control and Women's Empowerment (DPMGP4).A qualitative approach is the method of this research with informants coming from the person in charge of Sikula Geutanyoe program, which is a Student Organization Capacity Building Program for the State Administration Student Association (PPK ORMAWA HIMADISTRA) at Teuku Umar University in collaboration with DPMGP4. Data was collected by means of interviews, observation and documentation. Determination of informants with purposive sampling technique and totaling 5 people came from the person in charge of the Sikula Geutanyoe Program 3 informants and from DPMGP4 2 informants. The data that has been obtained is then analyzed through 3 stages, the first is selecting data, then presenting the data and the last step is making conclusions. The results of the research show that optimizing the role of women has been carried out through the "Sikula Geutanyoe" program. The results of this study are that optimizing the role of women has been carried out through the "Sikula Geutanyoe" program. The role of DPMGP4 of Nagan Raya Regency in empowering women is carried out through partnership programs and training provided to women by emphasizing understanding of 8 family functions, namely religious, socio-cultural, love, protection, reproductive, economic, socialization. and education, and environmental development. There is optimism from the women who are involved both in the training and in the management of the "Sikula Geutanyoe" Program to rise together and become one of the agents of development so that they can improve their standard of living for the better.ABSTRAKPerempuan mempunyai kemampuan memegang peranan sebagai aktor strategis pada pembangunan Indonesia ini, begitu juga dengan perempuan yang berasal dari Kabupaten Nagan Raya. Penelitian mempunyai tujuan menggali lebih dalam terkait optimalisasi peran perempuan dalam program pemberdayaan perempuan yang bermitra dengan Dinas Pemberdayaan Masyarakat, Gampong, Pengendalian Penduduk dan Pemberdayaan Perempuan (DPMGP4). Pendekatan kualitatif menjadi metode penelitian ini dengan informan yang berasal dari penanggungjawab program Sikula Geutanyoe yang merupakan Program Peningkatan Kapasitas Organisasi Kemahasiswaan Himpunan Mahasiswa Ilmu Administrasi Negara (PPK ORMAWA HIMADISTRA) Universitas Teuku Umar yang bekerjasama dengan DPMGP4. Data dikumpulkan dengan cara interview, pengamatan dan dokumentasi. Penentuan informan dengan teknik purposive sampling dan berjumlah 5 orang yang berasal dari penanggungjawab Program Sikula Geutanyoe 3 informan serta dari DPMGP4 2 informan. Data yang telah didapat lalu dianalisi melalui 3 tahapan, pertama penyeleksian data, lalu penyajian data dan Langkah terakhir dengan membuat kesimpulan. Hasil dari penelitian menunjukkan bahwa pengoptimalisasi peran perempuan telah dilakukan melalui program “Sikula Geutanyoe”. Peran DPMGP4 Kabupaten Nagan Raya dalam memberdayakan perempuan dilakukan dengan program kemitraan dan pelatihan yang diberikan kepada kaum perempuan dengan menekankan pemahaman pada 8 fungsi keluarga, yaitu keagamaan, sosial budaya, cinta kasih, perlindungan, reproduksi, ekonomi, sosialisasi dan pendidikan, dan pembinaan lingkungan. Adanya optimisme dari para perempuan yang terlibat baik dalam pelatihan maupun dalam kepengurusan Program “Sikula Geutanyoe” untuk bangkit bersamasama dan menjadi salah satu agen pembangunan sehingga dapat meningkatkan taraf hidup menjadi lebih baik.